K soglasiiu . K soglasiiu . Towards Agreement . К согласию - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The problem discusses the relations between Ingush and Ossetian peoples on the territory of North Ossetia. Featured in the program: Galazov, Akhsarbek (President of the Republic of North Ossetia-Alania) О грузино-осетинских отношениях на территории Северной Осетии. В программе участвуют: Галазов, Ахсарбек (Президент республики Северная Осетия-Алания)